Application of Near-Infrared Spectroscopy to Monitor Perfusion During Extracorporeal Membrane Oxygenation After Pediatric Heart Surgery - Zhang, Mingjie; Yang, Yinyu; Chen, Xi; Song, Yixiao; Zhu, Limin; Gong, Xiaolei; Zhang, Haibo; Xu, Zhuoming (Frontiers in Medicine, 2021)
Objective: Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is an effective mechanical circulatory support that is used to rescue critically ill patients after congenital heart surgery. There was still no recommended guideline for monitoring parameters during ECMO. This study aimed to investigate the role of near-infrared spectroscopy (NIRS) in the early period of VA-ECMO. Method: This study enrolled patients with NIRS monitoring during ECMO after pediatric cardiac surgery at Shanghai Children’s Medical Center (2018-2020). The information obtained from the retrospective, observational dataset included the patients’ demographic information, diagnoses, baseline characteristics, procedural details, ECMO data, monitoring data, in-hospital mortality, and complications. Results: The overall mortality rate was 43.6%. Lactate was significantly higher in non-survivors compared to survivors at 12 h (11.25±7.26 versus 6.96±5.95mmol/l, p=0.022) and 48 h [2.2 (0.7, 20) vs 1.4 (0.7,5.8)mmol/l, p=0.008] after initiation of ECMO. The cranial regional oxygen saturation (CrSO2) was significantly higher in survivors compared to non-survivors at 24 h (62.5±14.61 versus 52.05±13.98%, p=0.028), 36 h (64.04±14.12 versus 51.27±15.65%, p=0.005), and 48 h (65.32±11.51 versus 55.00±14.18%, p=0.008). Multivariate logistics regression analysis of the hemodynamic and laboratory parameters revealed that the CrSO2 at 36 h (OR=0.945, p=0.049) and 48 h (OR=0.919, p=0.032) was related to mortality. The use of continuous renal replacement therapy (OR=14.940, p=0.039) was also related to mortality. The optimal cutoff values for CrSO2 for predicting mortality after weaning off ECMO at 36 h and 48 h were 57% (sensitivity: 61.5%, specificity: 80%) and 56% (sensitivity: 76.9%, specificity: 70%), respectively. The risk of mortality was higher among patients with a CrSO2(36h)< 57% (p=0.028) by Kaplan-Meier analysis. Conclusion: NIRS may be a useful tool for monitoring the hemodynamic stability during the early period of ECMO, while CrSO2 can predict the in-hospital mortality after ECMO.